The Effect of the Problem Based Learning Model on Students' Critical Thinking Skills in Geography at SMAN 1 Trenggalek, Indonesia - Rafinda, Rosalia Rica; Sumarmi, Sumarmi; Ishak, Nor Asniza (PT. Pena Produktif Kreatif, 2024)
The findings showed that the Problem Based Learning model has a positive and significant effect on students' critical thinking skills, the result of the significance (2-tailed) in the two comparison classes, namely the experimental class and the control class, is 0.000. In addition, there is also a probability that shows a number of 0.000 less than 0.05, on the critical thinking ability of students, the results of the average obtain score in the experimental class are (20.2) while the class that is used as the control class is (7.7). Based on these data, it can be proved that H0 is rejected and H1 is accepted. This can be interpreted that this problem-based learning model affects students' ability to think critically in the learning process of Geography subjects at SMAN 1 Trenggalek. This is because the syntax of the PBL learning model is able to encourage students' critical thinking skills, so that students' critical thinking skills can increase. Therefore, this learning model is highly recommended to be implemented in the learning process of Geography subjects.